Integration of Behavioral and Oral Health in Health Centers - Candace L. H. Owen; Huong Le; Rebecca A. Cornille (Journal of the California Dental Association)
Introduction In recent years, the demand for behavioral health services has grown. There is increased need for early access to behavioral health and improved understanding of the relationship between oral health and behavioral health.Objective The objective of this article is to provide understanding of how oral health and behavioral health can be integrated in health centers.Methods This paper discusses the relationship between oral health and behavioral health, reviews the history of integration, and highlights health centers that have developed systems for dental professionals to engage in two aspects of integration of behavioral and oral health (IBOH) – behavioral health screenings and referral managementResults Health centers across the country are implementing strategies to increase access to oral health and behavioral health care through integration of the two disciplines.Conclusion In health centers, disciplines like primary medical care, dental care, behavioral health, and pharmacy are often co-located. This creates a unique opportunity to provide integrated care, including oral health and behavioral health.